Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dan Pemanfaatan Media Canva Untuk Meningkatkan Hasil Belajar IPAS Murid Kelas V.B di UPT SPF SDN Gunung Sari I Makassar - Weda, Rahma; Yunus, Muh; Iskandar, Arifuddin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to improve the learning outcomes of science and science through the application of the Two Stay Two Stray type cooperative learning model and the use of Canva media in grade V.B at UPT SPF SDN Gunung Sari I Makassar. The research method used is classroom action research which consists of planning, implementation, observation, and reflection to continue to make improvements and evaluations. The subject of this study is students of class V.B at UPT SPF SDN Gunung Sari I Makassar with a total of 22 students, consisting of 8 boys and 14 girls. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of the Two Stay Two Stray type cooperative learning model and the use of Canva media can improve student learning outcomes in science and science learning in class V.B at UPT SPF SDN Gunung Sari I Makassar. This is evidenced by the increase in the average percentage of student learning outcomes in each cycle. In the first cycle, the average student learning outcome was 67 with a learning completion percentage of only 50%. In cycle II, there was a significant increase with the average student learning outcome of 81 with the percentage of learning completion having reached 86%. This means that the average percentage of student learning outcomes has exceeded the set success criteria of 75%.